Opportunities and prospects in the diagnosis of functional intestinal pathology - A.A. Khanukov; N.S. Fedorova (Zaslavsky O.Yu., 2017)
Irritable bowel syndrome (IBS) is the most commonly diagnosed gastrointestinal condition in the 21st century and also the most common cause for referral to gastroenterology clinics. Various mechanisms and theories have been proposed about its etiology, but the biopsychosocial model is the most currently accepted for IBS. The complex of symptoms would be the result of the interaction between psychological, behavioral, psychosocial and environmental factors. The diagnosis of IBS is not confirmed by specific tests. It is made using criteria based on clinical symptoms, such as Rome criteria, unless the symptoms are thought to be atypical. Today, the Rome criteria IV are the most optimal standard for the diagnosis of IBS. At the moment, there are no specific laboratory markers for the diagnosis of IBS. However, a number of different symptoms in IBS patients were demonstrated in recent years, some of which can be used in the future as diagnostic criteria. One of them is the method for the assessment of fecal calprotectin, which demonstrated a high diagnostic value, as a marker of inflammation in differential diagnosis between inflammatory bowel diseases and functional gastrointestinal disorders.